Genetically Modified Crops and Agricultural Development - Qaim, Matin; SpringerLink (Online service) (New York : Palgrave Macmillan US (Imprint), 2016)
This book analyzes the impacts of current and possible future GM crop applications and shows that these technologies can contribute substantially to sustainable agricultural development and food security.
1. Introduction -- 2. Plant Breeding and Agricultural Development -- 3. Potentials and Risks of GM Crops -- 4. Adoption and Impacts of GM Crops -- 5. New and Future GM Crop Applications -- 6. GM Crop Regulation -- 7. The Complex Public Debate -- 8. Conclusions.
Keywords: Environmental economics; Development economics; Agriculture; Agricultural Economics